2022
DOI: 10.3390/genes13122267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Melanocortin 4-Receptor Ile269Asn Mutation on Weight Loss Response to Dietary, Phentermine and Bariatric Surgery Interventions

Abstract: The loss of function melanocortin 4-receptor (MC4R) Ile269Asn mutation has been proposed as one of the most important genetic contributors to obesity in the Mexican population. However, whether patients bearing this mutation respond differently to weight loss treatments is unknown. We tested the association of this mutation with obesity in 1683 Mexican adults, and compared the response of mutation carriers and non-carriers to three different weight loss interventions: dietary restriction intervention, phenterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…Censani et al, and Salazar-Valencia et al [5,6,31] did not show a relationship between mutations of the leptin-melanocortin pathway genes and the extent of weight loss within 1 year after surgery in Caucasian and Latino patients, which was consistent with the results of our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Censani et al, and Salazar-Valencia et al [5,6,31] did not show a relationship between mutations of the leptin-melanocortin pathway genes and the extent of weight loss within 1 year after surgery in Caucasian and Latino patients, which was consistent with the results of our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…After grouping all research results based on follow‐up time, we found that this controversy probably arose from the results of a weight‐tracking follow‐up time within 1 year after surgery. The results of Cooiman et al, Censani et al, and Salazar‐Valencia et al [5, 6, 31] did not show a relationship between mutations of the leptin‐melanocortin pathway genes and the extent of weight loss within 1 year after surgery in Caucasian and Latino patients, which was consistent with the results of our analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations